2010
DOI: 10.1083/jcb.201003053
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis of acid sphingomyelinase by wounded cells promotes endocytosis and plasma membrane repair

Abstract: Lysosomal enzyme acid sphingomyelinase is released extracellularly when cells are wounded, converting sphingomyelin to ceramide and inducing endosome formation to internalize membrane lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
405
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(436 citation statements)
references
References 46 publications
(96 reference statements)
19
405
5
3
Order By: Relevance
“…These results indicate that sphingomyelinase functions downstream of the Ca 2+ -dependent step of plasma membrane repair. This finding is fully consistent with our previously proposed model, which postulates that Ca 2+ flowing through transmembrane pores triggers exocytosis of lysosomes and ASM release, which cleaves sphingomyelin on the outer leaflet of the plasma membrane, generating ceramide and promoting pore removal by endocytosis 22,19 . The fact that addition of purified SM bypasses the need for Ca 2+ strongly reinforces the view that under physiological conditions Ca 2+ -regulated exocytosis of lysosomes is the source of the sphingomyelinase activity required to promote endocytosis.…”
Section: Representative Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These results indicate that sphingomyelinase functions downstream of the Ca 2+ -dependent step of plasma membrane repair. This finding is fully consistent with our previously proposed model, which postulates that Ca 2+ flowing through transmembrane pores triggers exocytosis of lysosomes and ASM release, which cleaves sphingomyelin on the outer leaflet of the plasma membrane, generating ceramide and promoting pore removal by endocytosis 22,19 . The fact that addition of purified SM bypasses the need for Ca 2+ strongly reinforces the view that under physiological conditions Ca 2+ -regulated exocytosis of lysosomes is the source of the sphingomyelinase activity required to promote endocytosis.…”
Section: Representative Resultssupporting
confidence: 81%
“…Using the FM1-43 imaging assay, we previously showed that cells deficient for the lysosomal enzyme ASM and exposed to SLO wounding in the presence of Ca 2+ have a plasma membrane defect is rescued by extracellular addition of the recombinant human enzyme 19 . Since the human lysosomal ASM has a low pH optimum, we investigated whether resealing could also be restored adding SM purified from Bacillus cereus (Sigma), which is fully active at neutral pH.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that exocytosis of acid sphingomyelinase by wounded cells promotes endocytosis and plasma membrane repair (39). Thus, the local elevation of Cer on the plasma membrane is important for endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface targeting of P2X4Rs by lysosomes has recently been shown to involve the chemokine CC2 [68]. It is well established that injury to a cell induces lysosome exoctyosis [35,38,57,66]; thus, it is conceivable that cell damage resulting from injury to a nerve might mobilize P2X4Rs from lysosomes to the microglial cell surface.…”
Section: Introductionmentioning
confidence: 99%